Haplotypes of the inducible nitric oxide synthase gene are strongly associated with exhaled nitric oxide levels in adults: a population-based study. Issue 7 (11th April 2014) - Dahgam, Santosh; Modig, Lars; Torinsson Naluai, Åsa; Olin, Anna-Carin; Nyberg, Fredrik
Abstract : Background: Previous genetic association studies have reported evidence for association of single-nucleotide polymorphisms (SNPs) in the NOS2 gene, encoding inducible nitric oxide synthase (iNOS), to variation in levels of fractional exhaled nitric oxide (FENO) in children and adults. In this study, we evaluated 10 SNPs in the region of chromosome 17 from 26.07 Mb to 26.13 Mb to further understand the contribution of NOS2 to variation in levels of FENO. Methods: In a cohort of 5912 adults 25–75 years of age, we investigated the relationship between NOS2 haplotypes and FENO, and effect modification by asthma. Results: Seven common (frequency ≥5%) haplotypes (H1–H7) were inferred from all possible haplotype combinations. One haplotype (H3) was significantly associated with lower levels of FENO: −5.8% (95% CI −9.8 to −1.7; p=0.006) compared with the most common baseline haplotype H1. Two haplotypes (H5 and H6) were significantly associated with higher levels of FENO: +10.7% (95% CI 5.0 to 16.7; p=0.0002) and +14.9% (95% CI 10.6 to 19.3; p=7.8×10 −13 ), respectively. The effect of haplotype H3 was mainly seen in subjects with asthma (−21.6% (95% CI −33.5 to −5.9)) and was not significant in subjects without asthma (−4.2% (95% CI −8.4 to 0.2)). The p value for interaction between H3 and asthma status was 0.004. Conclusions: Our findings suggest that several common haplotypes in the NOS2 gene contribute to variation in FENO in adults. We also saw some evidence of effect modification by asthma status on haplotype H3.